Corporate Integrity Disclosure in the Annual Report: A Study on Malaysian Federal Statutory Bodies - Siti Zabedah, Saidin; Hasnah, Haron (Universiti Malaysia Pahang, 2017)
The objective of this study is to discover the availability of integrity disclosures in the annual reports of Malaysian federal statutory bodies by focusing on the non-financial section of the reports. The sample was selected from a list of federal statutory bodies issued in the Auditor General Report for 2015. A total of 60 federal statutory bodies’ annual reports were selected randomly, based on their availability on the internet. Content analysis of the non-financial section was used to explore for the existence of integrity being disclosed in the annual reports based on the initiatives taken by the government on the implementation of integrity culture in public sector organizations. Finding from this study reveals that, out of 60 federal statutory bodies, 45 of them (75%) disclosed some elements of integrity in their annual report although no specific requirement for such disclosure is required. Majority of the federal statutory bodies have established their integrity unit and provide other information on integrity in their annual report such as integrity enculturation programs, workshops on integrity and reinforcing human capital capability and capacity with integrity. Though this paper provides some useful insights into ‘integrity’ disclosures among public sector organizations, it is limited to the federal statutory bodies and the non-financial information in the annual reports only.